Предмет: Алгебра, автор: hote

Решите неравенство
(x^2-x+1) / (x-1) + (x^2-3x+1 )/ (x-3) > 2x - (1/ (4x+8))

Ответы

Автор ответа: Аноним
0
 frac{x^2-x+1}{x-1}+ frac{x^2-3x+1}{x-3} textgreater  2x- frac{1}{4x+8}   \  frac{x^2-x+1}{x-1} + frac{x^2-3x+1}{x-3} + frac{1}{4(x+2)} -2x textgreater  0\  frac{(x^2-x+1)(x-3)4(x+2)+(x^2-3x+1(x-1)4(x+2)+(x-1)(x-3)}{4(x-1)(x-3)(x+2)} -2x textgreater  0
 frac{4x^4-8x^3-16x^2+20x-24+4x^4-8x^3-16x^2+28x-8+x^2-4x+3}{4(x-1)(x-3)(x+2)} -2x textgreater  0\ frac{8x^4-16x^3-31x^2+44x-29}{4(x-1)(x-3)(x+2)} -2x textgreater  0\ frac{8x^4-16x^3-31x^2+44x-29-8x(x-1)(x-3)(x+2)}{4(x-1)(x-3)(x+2)}  textgreater  0
 frac{-8x^4+16x^3+40x^2-48x+8x^4-16x^3-31x^2+44x-29}{4(x-1)(x-3)(x+2)} textgreater  0\  frac{9x^2-4x-29}{4(x-1)(x-3)(x+2)}  textgreater  0

Рассмотрим функцию
 f(x)=frac{9x^2-4x-29}{4(x-1)(x-3)(x+2)}
x1 ≠ 1;    x2≠3;     x3≠-2
D(f)=(-infty;-2)cup(-2;1)cup(1;+infty)

Приравниваем её к нулю
 frac{9x^2-4x-29}{4(x-1)(x-3)(x+2)} =0 \ 9x^2-4x-29=0\ D=b^2-4ac=(-4)^2-4cdot9cdot(-29)=1060;,,, sqrt{D} =2 sqrt{265}
x_1_,_2= dfrac{2pm sqrt{265} }{9}


Ответ: (-2;frac{2- sqrt{265} }{9})cup(1;frac{2+ sqrt{265} }{9})cup(3;+infty)
Приложения:
Похожие вопросы
Предмет: Английский язык, автор: Nargiz2506